2015
DOI: 10.5811/westjem.2015.9.27276
|View full text |Cite
|
Sign up to set email alerts
|

Are Live Ultrasound Models Replaceable? Traditional vs. Simulated Education Module for FAST Exam

Abstract: IntroductionThe focused assessment with sonography for trauma (FAST) is a commonly used and life-saving tool in the initial assessment of trauma patients. The recommended emergency medicine (EM) curriculum includes ultrasound and studies show the additional utility of ultrasound training for medical students. EM clerkships vary and often do not contain formal ultrasound instruction. Time constraints for facilitating lectures and hands-on learning of ultrasound are challenging. Limitations on didactics call for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
64
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(67 citation statements)
references
References 12 publications
2
64
0
1
Order By: Relevance
“…Devices and simulators [104][105][106][107][108][109][110][111][112][113][114][115][116] The primary objective of these papers was to describe or evaluate ultrasound simulators (or 'phantoms') or devices adjunctive to the ultrasound machine itself. Ultrasound simulators are models of human anatomy designed to provide a means of practicing ultrasound skills where practice on a human is impractical, dangerous or unethical.…”
Section: Learning Category-incorporation Of Ultrasound Into Teaching mentioning
confidence: 99%
See 2 more Smart Citations
“…Devices and simulators [104][105][106][107][108][109][110][111][112][113][114][115][116] The primary objective of these papers was to describe or evaluate ultrasound simulators (or 'phantoms') or devices adjunctive to the ultrasound machine itself. Ultrasound simulators are models of human anatomy designed to provide a means of practicing ultrasound skills where practice on a human is impractical, dangerous or unethical.…”
Section: Learning Category-incorporation Of Ultrasound Into Teaching mentioning
confidence: 99%
“…Ultrasound simulators are models of human anatomy designed to provide a means of practicing ultrasound skills where practice on a human is impractical, dangerous or unethical. Our search found studies that tested both commercially available simulators [104][105][106][107][108] and institutions that built their own simulators with varying degrees of complexity [109][110][111].…”
Section: Learning Category-incorporation Of Ultrasound Into Teaching mentioning
confidence: 99%
See 1 more Smart Citation
“…The results concur with previous studies on the benefits and the noninferiority of ultrasound simulators in the training of novice ultrasound learners. In 2016, Silva et al and Bentley et al found no significant difference in the ultrasound skills and knowledge of students trained using an ultrasound simulator versus students trained using live models. In addition, Tolsgaard et al showed significant improvement in the performance of gynecologic ultrasound examinations by residents when the use of an ultrasound simulator was added to their clinical training.…”
Section: Discussionmentioning
confidence: 99%
“…Of the 14 studies in the review, only 5 included a control group, and only 2 of those were randomized. Since this publication, multiple controlled randomized trials have reported the potential benefits of ultrasound simulators . In addition, ultrasound simulators allow trainees to practice multiple times the same ultrasound modality without the need of supervisors or models.…”
Section: Discussionmentioning
confidence: 99%